Mythos in Claude Lévi-Strauss - Ahmet Uğurlu (İnsan & Toplum)
Humankind has been continuously trying to interpret the universe they live in and the existence they have since coming into being. How the sky, the earth, the seas and the mountains were created have an important place in this process of interpretation as something related to the creation of the universe. Humankind has also tried to understand the struggle between goodness and evil, and how humanity came into existence. In this process of interpretation, human efforts to understand these things were not much based on factual truth. Rather, in prehistoric times, the human struggle to understanding life and the universe was a struggle that used surreal symbols. For this reason, myths may be defined as sacred legends which both explain the existence of community of a certain region or of humankind. Thus, mythos should be considered as a system of thinking and discourse of the transition period from primitive life to culture. Archaic people expressed the form of rational thinking they experienced though nature with mythos fiction so that they could grasp society and what it was. Lévi Strauss has the idea that the logical structure of the modern world and the note system in music can help us to understand mythos. In light of this, it will be noticed that there has never been a great difference between primitive and modern men and finding out their similarity will help us to find answer questions about the vagueness of humankind.